Holiness Belief of Kyrgyz - Zuuridinov, Oskonbay (Scientific Journal of Faculty of Theology, 2018)
Yiyk is synonym of holy in the Kyrgyz language. In this article we wrote about holiness belief of Kyrgyz nationality. The holiness beliefs of traditional Kyrgyz muslims are their ancient beliefs and it known as shamanism. We compared the holy of Islam and traditional Kyrgyz muslims.